2022
DOI: 10.1038/s41586-021-04343-z
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen trapping and embrittlement in high-strength Al alloys

Abstract: Ever more stringent regulations on greenhouse gas emissions from transportation motivate efforts to revisit materials used for vehicles1. High-strength aluminium alloys often used in aircrafts could help reduce the weight of automobiles, but are susceptible to environmental degradation2,3. Hydrogen ‘embrittlement’ is often indicated as the main culprit4; however, the exact mechanisms underpinning failure are not precisely known: atomic-scale analysis of H inside an alloy remains a challenge, and this prevents … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(56 citation statements)
references
References 47 publications
8
48
0
Order By: Relevance
“…First-principles studies also propose that the hydrogen at Σ3 twins leads to a mild increase in the grain boundary energy [49], facilitating grain boundary decohesion and hence the critical stress to fracture the material, similar to what was previously observed for e.g. Al-alloys [50].…”
Section: Fig 2 (A) Electron Backscatter Diffraction-inverse Pole Figu...supporting
confidence: 75%
“…First-principles studies also propose that the hydrogen at Σ3 twins leads to a mild increase in the grain boundary energy [49], facilitating grain boundary decohesion and hence the critical stress to fracture the material, similar to what was previously observed for e.g. Al-alloys [50].…”
Section: Fig 2 (A) Electron Backscatter Diffraction-inverse Pole Figu...supporting
confidence: 75%
“…Bauxite, as the main raw material of alumina and metal aluminum, plays an irreplaceable role in the manufacturing fields of spacecrafts [1,2], automobiles [3,4], and so on. At the same time, due to the thermostability and wear resistance of bauxite, it has a wide range of application value in the fields of refractory [5,6], polishing powder [7], advanced grinding wheel, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminium alloys are also not immune to hydrogen ingress and when hydrogen is introduced as a solute, it easily diffuses and segregates to crystalline defects [34,35]. Ab initio calculations have shown that hydrogen atoms strongly interact with vacancies in aluminium [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies focusing on the hydrogen/vacancy interactions in metals have shown that hydrogen decreases the formation energy of vacancy clusters containing hydrogen [33,37] and the vacancy migration energy [39]. Hydrogen may also delay the clustering of solutes and the coarsening of precipitates in some Al alloys [35,40]. Therefore, it is critical to understand how these interactions impact the kinetic and thermodynamic of precipitates in aluminium alloys (which may evolve even at room temperature) to predict microstructural evolutions and eventually to reduce the damaging effect of hydrogen.…”
Section: Introductionmentioning
confidence: 99%